Composite solid electrolyte containing oxygen vacancy catalyst as well as preparation method and application of composite solid electrolyte
By introducing the oxygen-containing vacancies catalyst PrOx-V0 into the polymer solid electrolyte, the problem of low conductivity of polymer solid electrolyte is solved, the number of migration of sodium ions and the stability of electrode interface is improved, and the all-solid sodium battery is realized at room temperature Under the possibility of efficient work.
Patent Information
- Application Number
- CN202411184858.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-01-03
AI Technical Summary
The low ion conductivity and low ion migration of polymer solid electrolytes lead to the need for all-solid sodium batteries to work properly under high temperature and high pressure, which hinders their large-scale application.
The oxygen-containing vacancies catalyst PrOx-V0 is used as an additive for the composite solid electrolyte. By combining with polymer and metal sodium salt, the dissolution and dissociation of the sodium salt is promoted, the conductivity and migration number are improved, and a stable electrolyte/electrode interface is constructed. Improve interface compatibility.
The sodium ion conductivity and migration number of the composite solid electrolyte are significantly improved, the stability of the electrode and electrolyte interface is optimized, the growth of sodium dendrites is inhibited, and the circulation and rate performance of all-solid metal sodium batteries are enhanced.
Smart Images

Figure CN119253044A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a composite solid electrolyte containing an oxygen vacancy catalyst, and a preparation method and application thereof. Background Art
[0002] Sodium-ion battery systems have received extensive attention in recent years due to their abundant resources, low price, environmental friendliness, and electrochemical properties similar to those of lithium-ion batteries, providing a new option for electrochemical energy storage. However, traditional liquid sodium batteries currently contain organic liquid electrolytes, which have poor thermal stability and are flammable. When the battery is abused and generates heat, there are safety hazards such as leakage, fire, and explosion. All-solid-state sodium metal batteries use solid polymers instead of traditional organic electrolytes as electrolytes, which can greatly increase the battery energy density and extend the battery life while improving the safety of sodium batteries.
[0003] Polymer solid electrolytes have the advantages of good flexibility and stability to metallic sodium negative electrodes, and have attracted widespread attention. However, due to the high degree of crystallinity of the polymer itself, it has extremely low room temperature ionic conductivity, low ion migration number, poor high-voltage stability and poor mechanical properties, resulting in all-solid-state sodium batteries needing to work properly under high temperature and high pressure, which seriously hinders its large-scale application. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of low ionic conductivity and low ion migration number of polymer solid electrolyte itself, and to provide a composite solid electrolyte containing oxygen vacancy catalyst and its preparation method and application. PrOx-V0 oxygen vacancies have strong affinity with salt anions, which can promote the dissolution of sodium salts and release more free sodium ions; PrOx-V0 destroys the structural stability of PEO chains, reduces the crystallinity of PEO, expands the amorphous region of PEO, and improves the conductivity of PEO itself; a stable electrolyte / electrode interface is constructed to improve interface compatibility. It promotes the dissociation of sodium salts, so that salt anions form an in-situ NaF stable interface SEI layer, uniform ion flux, reduce interface polarization, and inhibit sodium dendrites.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A composite solid electrolyte containing an oxygen vacancy catalyst, the composite solid electrolyte comprising a polymer, a metal sodium salt, and an inorganic additive, wherein the inorganic additive is an oxygen vacancy catalyst PrOx-V0, and the ratio of the mass of the inorganic additive to the total mass of the polymer and the metal sodium salt is 1-15:100.
[0007] Further, the polymer is one or more of polyethylene oxide, poly(vinylidene fluoride-co-hexafluoropropylene), polymethyl methacrylate, and polyacrylonitrile, and the metal sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bis(trifluoromethanesulfonyl imide), and sodium bis(difluorosulfonyl imide). The ratio of the polymer to the metal sodium salt is a conventional ratio.
[0008] Furthermore, the composite solid electrolyte consists of polyethylene oxide, sodium bis(trifluoromethanesulfonyl)imide and PrOx-V0.
[0009] Furthermore, the ratio of the mass of the inorganic additive to the total mass of the polymer and the metal sodium salt is 5:100.
[0010] A method for preparing the composite solid electrolyte containing oxygen vacancy catalyst as described above, the method comprising:
[0011] Step 1: Preparation of oxygen vacancy catalyst PrOx-V0:
[0012] (1) preparing a solution of a metal salt containing Pr with a concentration of 0.02-0.05M, preferably 0.025M, using a mixed solvent of water and ethanol in a volume ratio of 1:1-4 (preferably 1:2) as a solvent, placing the solution in a hydrothermal kettle, adding urea, stirring and mixing at room temperature to obtain a light green mixture; the mass ratio of the metal salt containing Pr to urea is 1:1-4, preferably 1:2;
[0013] (2) Slowly add NaOH solution to the above solution to adjust the pH value to between 8.5 and 9.5, and then continue stirring for 1 hour;
[0014] (3) closing the hydrothermal reactor, placing it in an oven at 120-160° C., heating for 1-4 h, preferably heating at 140° C. for 2 h, cooling naturally, collecting the precipitate by centrifugation, and drying it in an oven at 60° C. overnight to obtain a precursor;
[0015] (4) placing the precursor in a tube furnace, heating it to 450-650° C. under an inert atmosphere and calcining it for 2-6 h, preferably calcining it at 550° C. for 2 h, and then grinding it to obtain an oxygen vacancy catalyst PrOx-V0 after natural cooling;
[0016] Step 2: Preparation of composite solid electrolyte: The conventional solution casting method is used for preparation, that is, the polymer, metal sodium salt and oxygen vacancy catalyst are first completely dissolved in a volatile solvent, and after sufficient stirring and mixing at room temperature, the resulting mixed solution is poured into a mold, and allowed to stand at room temperature to allow the solvent to evaporate naturally, and finally transferred to a vacuum drying oven, heated to 60-80°C and dried for 10-12 hours, and after cutting, a composite solid electrolyte containing oxygen vacancy catalyst is obtained.
[0017] Furthermore, in step one (1), the metal salt containing Pr is one or more of praseodymium nitrate hexahydrate, praseodymium oxalate decahydrate, praseodymium phosphate, and praseodymium sulfate octahydrate.
[0018] Furthermore, in step 2, the volatile solvent is acetonitrile, dimethylformamide, anisole, dichloroethane, etc.
[0019] An application of the composite solid electrolyte containing oxygen vacancy catalyst is to use the composite solid electrolyte in the preparation of an all-solid-state metal sodium battery, wherein the all-solid-state metal sodium battery comprises a composite solid electrolyte, a metal sodium negative electrode and a positive electrode.
[0020] Furthermore, the metallic sodium negative electrode is one of metallic sodium foil, sodium sheet, sodium alloy, hard carbon or titanium-based negative electrode; the positive electrode is a composite of positive electrode active material, binder and conductive agent coated on a current collector.
[0021] Further, the current collector is aluminum foil, carbon-coated aluminum foil or stainless steel foil; the positive electrode active material is at least one of sodium iron phosphate, sodium vanadium phosphate, sodium titanium phosphate, sodium iron sulfate, sodium iron pyrophosphate, sodium ion fluorophosphate, sodium manganese oxide, sodium vanadium fluorophosphate; the binder is at least one of polyvinylidene fluoride, polyamide, polyvinyl alcohol, and carboxymethyl cellulose; the conductive agent is at least one of carbon black, Ketjen black, and super P. Generally speaking, in the composite of the positive electrode active material, the binder and the conductive agent, the mass ratio of the positive electrode active material, the binder and the conductive agent is 8:1:1.
[0022] The positive electrode specifically recommended by the present invention is prepared by the following steps:
[0023] (1) Mix and grind the positive electrode active material, binder and conductive agent in a mass ratio of 8:1:1, and take an appropriate amount of N-methylpyrrolidone (NMP) to mix the above materials evenly to obtain a mixed slurry with a certain fluidity;
[0024] (2) Use a 50-100 μm scraper to evenly scrape the mixed slurry onto the current collector, dry it in vacuum at 100-120°C for 10-12 hours, and then roll it to obtain a pole piece of uniform thickness. Then cut it into a shape of appropriate size and put it in a glove box for use.
[0025] The beneficial effects of the present invention compared to the prior art are:
[0026] (1) In the composite solid electrolyte provided by the present invention, the additive oxygen vacancy catalyst has a large number of oxygen vacancies, and there is a strong interaction between the surface oxygen vacancies and the sodium salt anions, which changes the local Na + environment, which helps the transport of sodium ions.
[0027] (2) The oxide catalyst PrOx-V0 is introduced into the polymer. As an inorganic solid filler, it can increase the concentration of sodium ion conductive amorphous in the polymer phase, accelerate the migration of sodium ions on the polymer chain segments, and improve the ion migration number of the composite solid electrolyte.
[0028] (3) The inorganic material / polymer interface in the composite electrolyte can construct a new sodium ion migration path, thereby improving the sodium ion conductivity and migration number of the composite electrolyte.
[0029] (4) During the charge and discharge cycle of the composite electrolyte, the oxygen vacancies PrOx-V0 can optimize the interfacial stability between the negative electrode and the electrolyte, promote the dissociation of the sodium salt, and enable the salt anions to form a NaF-rich protective layer on the surface of the metal sodium electrode, thereby achieving more uniform sodium deposition at the interface, enhancing the interfacial stability between the electrode and the electrolyte, and obtaining an all-solid-state metal sodium battery with better cycle performance.
[0030] (5) The mechanical properties of the composite solid electrolyte can inhibit the growth of dendrites on the surface of the sodium negative electrode during the cycle and effectively reduce the interfacial polarization and impedance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a multi-rate charge and discharge curve diagram of the Na / / NFPP battery with polymer solid electrolyte in Example 1 of the present invention;
[0032] Figure 2 This is a multi-rate charge and discharge curve diagram of the Na / / NFPP battery with polymer solid electrolyte in Example 2 of the present invention;
[0033] Figure 3 This is a multi-rate charge and discharge curve diagram of the Na / / NFPP battery with polymer solid electrolyte in Example 3 of the present invention;
[0034] Figure 4 This is a multi-rate charge and discharge curve diagram of the Na / / NFPP battery with polymer solid electrolyte in Example 4 of the present invention;
[0035] Figure 5 This is a multi-rate charge and discharge curve of the Na / / NFPP battery with polymer solid electrolyte in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the protection scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0037] Oxygen vacancies refer to the vacancy formed by the oxygen atom (oxygen ion) in the crystal lattice of metal oxides or other oxygen-containing compounds being detached, resulting in the lack of oxygen. In simple terms, oxygen vacancies refer to the defects left by the escape of oxygen ions from its crystal lattice. Oxygen vacancies are one of the most common defects in metal oxides.
[0038] The present invention synthesizes a praseodymium oxide PrOx-V0 catalyst containing oxygen vacancies, and prepares a composite solid electrolyte with different contents of PrOx-V0 additives by a solution casting method, which is applied to an all-solid-state sodium metal battery. By introducing simple additives and a simple and easy-to-operate preparation method, the electrochemical properties of the polymer PEO electrolyte are significantly improved, and the cycle performance and rate performance of the battery are improved.
[0039] The present invention uses oxygen-containing vacancy catalyst PrOx-V0 as a solid electrolyte additive, and there is a strong interaction between the surface oxygen vacancies and the sodium salt anions, which changes the local sodium ion environment, promotes the dissociation of the sodium salt and the migration of the sodium ions. At the same time, the introduction of the oxide catalyst PrOx-V0 into the polymer can increase the concentration of sodium ion conductive amorphous in the polymer phase; in addition, in the composite electrolyte, a new sodium ion migration path is constructed at the inorganic material / polymer interface, which improves the sodium ion conductivity and migration number of the composite electrolyte. The composite solid electrolyte has good mechanical properties, inhibits adverse side reactions at the interface between the electrolyte and the sodium metal, constructs a stable NaF interface layer, and obtains an all-solid-state metal sodium battery with better cycle performance.
[0040] Example 1
[0041] 1. Preparation of a composite solid electrolyte containing oxygen vacancy catalyst:
[0042] (1) preparing a solution with a concentration of 0.025 M of a metal salt containing Pr, using a mixed solvent of water and ethanol in a volume ratio of 1:2 as a solvent, placing the solution in a hydrothermal kettle, adding urea, stirring and mixing at room temperature to obtain a light green mixture; the mass ratio of the metal salt containing Pr to urea is 1:2;
[0043] (2) Slowly add NaOH solution to the above solution to adjust the pH value to between 8.5 and 9.5, and then continue stirring for 1 hour;
[0044] (3) closing the hydrothermal reactor, placing it in an oven at 140° C., heating it for 2 h, cooling it naturally, collecting the precipitate by centrifugation, and drying it in an oven at 60° C. overnight to obtain a precursor;
[0045] (4) placing the precursor in a tube furnace, heating it to 550° C. in an inert atmosphere and calcining it for 2 h, and then grinding it to obtain an oxygen vacancy catalyst PrOx-V0 after natural cooling;
[0046] According to Table 1, 15 mL of acetonitrile was used as the organic solvent, and 1.0 g of PEO (M v ≈600,000) and 0.3445 g of metal salt NaTFSI (M v =303.14), the molar ratio of PEO to metal salt is 20:1, 1.0% PrOx-V0 of the total mass of polymer matrix and metal salt is added, and stirred at room temperature for 24 hours; then poured into a polytetrafluoroethylene mold, allowed to stand at room temperature for 24 hours to evaporate a large amount of solvent; then vacuum dried at 60°C for 24 hours to obtain a composite solid electrolyte containing 1.0% PrOx-V0.
[0047] 2. A method for preparing a positive electrode sheet is as follows:
[0048] (1) 0.24 g of sodium ferric pyrophosphate, 0.03 g of polyvinylidene fluoride and 0.03 g of carbon black were mixed and ground in a ratio of 8:1:1, added to a certain amount of N-methylpyrrolidone (NMP), stirred at room temperature for 4-6 h, and mixed thoroughly to obtain a prepared slurry;
[0049] (2) The slurry is evenly coated on the carbon-coated aluminum foil, vacuum dried at 100-120°C for 10-12h, and then placed in a glove box for use.
[0050] 3. Assemble the positive electrode sheet, the sodium metal sheet and the above-mentioned solid electrolyte into an all-solid-state sodium metal battery in a glove box filled with argon (O2, H2O content are both <0.1ppm).
[0051] Example 2
[0052] 1. Preparation of a composite solid electrolyte containing oxygen vacancy catalyst:
[0053] (1) preparing a solution with a concentration of 0.025 M of a metal salt containing Pr, using a mixed solvent of water and ethanol in a volume ratio of 1:2 as a solvent, placing the solution in a hydrothermal kettle, adding urea, stirring and mixing at room temperature to obtain a light green mixture; the mass ratio of the metal salt containing Pr to urea is 1:2;
[0054] (2) Slowly add NaOH solution to the above solution to adjust the pH value to between 8.5 and 9.5, and then continue stirring for 1 hour;
[0055] (3) closing the hydrothermal reactor, placing it in an oven at 140° C., heating it for 2 h, cooling it naturally, collecting the precipitate by centrifugation, and drying it in an oven at 60° C. overnight to obtain a precursor;
[0056] (4) placing the precursor in a tube furnace, heating it to 550° C. in an inert atmosphere and calcining it for 2 h, and then grinding it to obtain an oxygen vacancy catalyst PrOx-V0 after natural cooling;
[0057] According to Table 1, 15 mL of acetonitrile was used as the organic solvent, and 1.0 g of PEO (M v ≈600,000) and 0.3445 g of metal salt NaTFSI (M v =303.14), the molar ratio of PEO to metal salt is 20:1, 5.0% PrOx-V0 of the total mass of polymer matrix and metal salt is added, and stirred at room temperature for 24 hours; then poured into a polytetrafluoroethylene mold, allowed to stand at room temperature for 24 hours to evaporate a large amount of solvent; then vacuum dried at 60°C for 24 hours to obtain a composite solid electrolyte containing 5.0% PrOx-V0.
[0058] 2. A method for preparing a positive electrode sheet is as follows:
[0059] (1) 0.24 g of sodium ferric pyrophosphate, 0.03 g of polyvinylidene fluoride and 0.03 g of carbon black were mixed and ground in a ratio of 8:1:1, added to a certain amount of N-methylpyrrolidone (NMP), stirred at room temperature for 4-6 h, and mixed thoroughly to obtain a prepared slurry;
[0060] (2) The slurry is evenly coated on the carbon-coated aluminum foil, vacuum dried at 100-120°C for 10-12h, and then placed in a glove box for use.
[0061] 3. Assemble the positive electrode sheet, the sodium metal sheet and the above-mentioned solid electrolyte into an all-solid-state sodium metal battery in a glove box filled with argon (O2, H2O content are both <0.1ppm).
[0062] Example 3
[0063] 1. Preparation of a composite solid electrolyte containing oxygen vacancy catalyst:
[0064] (1) preparing a solution with a concentration of 0.025 M of a metal salt containing Pr, using a mixed solvent of water and ethanol in a volume ratio of 1:2 as a solvent, placing the solution in a hydrothermal kettle, adding urea, stirring and mixing at room temperature to obtain a light green mixture; the mass ratio of the metal salt containing Pr to urea is 1:2;
[0065] (2) Slowly add NaOH solution to the above solution to adjust the pH value to between 8.5 and 9.5, and then continue stirring for 1 hour;
[0066] (3) closing the hydrothermal reactor, placing it in an oven at 140° C., heating it for 2 h, cooling it naturally, collecting the precipitate by centrifugation, and drying it in an oven at 60° C. overnight to obtain a precursor;
[0067] (4) placing the precursor in a tube furnace, heating it to 550° C. in an inert atmosphere and calcining it for 2 h, and then grinding it to obtain an oxygen vacancy catalyst PrOx-V0 after natural cooling;
[0068] According to Table 1, 15 mL of acetonitrile was used as the organic solvent, and 1.0 g of PEO (M v ≈600,000) and 0.3445 g of metal salt NaTFSI (M v =303.14), the molar ratio of PEO to metal salt is 20:1, 10.0% PrOx-V0 of the total mass of polymer matrix and metal salt is added, and stirred at room temperature for 24 hours; then poured into a polytetrafluoroethylene mold, allowed to stand at room temperature for 24 hours to evaporate a large amount of solvent; then vacuum dried at 60°C for 24 hours to obtain a composite solid electrolyte containing 10.0% PrOx-V0.
[0069] 2. The preparation method of the positive electrode sheet is the same as that of Example 1.
[0070] 3. Assemble the positive electrode sheet, the sodium metal sheet and the above-mentioned composite solid electrolyte containing different concentrations of PrOx-V0 into an all-solid-state sodium metal battery in a glove box filled with argon (O2, H2O content are both <0.1ppm).
[0071] Example 4
[0072] 1. Preparation of a composite solid electrolyte containing oxygen vacancy catalyst:
[0073] (1) preparing a solution with a concentration of 0.025 M of a metal salt containing Pr, using a mixed solvent of water and ethanol in a volume ratio of 1:2 as a solvent, placing the solution in a hydrothermal kettle, adding urea, stirring and mixing at room temperature to obtain a light green mixture; the mass ratio of the metal salt containing Pr to urea is 1:2;
[0074] (2) Slowly add NaOH solution to the above solution to adjust the pH value to between 8.5 and 9.5, and then continue stirring for 1 hour;
[0075] (3) closing the hydrothermal reactor, placing it in an oven at 140° C., heating it for 2 h, cooling it naturally, collecting the precipitate by centrifugation, and drying it in an oven at 60° C. overnight to obtain a precursor;
[0076] (4) placing the precursor in a tube furnace, heating it to 550° C. in an inert atmosphere and calcining it for 2 h, and then grinding it to obtain an oxygen vacancy catalyst PrOx-V0 after natural cooling;
[0077] According to Table 1, 15 mL of acetonitrile was used as the organic solvent, and 1.0 g of PEO (M v ≈600,000) and 0.3445 g of metal salt NaTFSI (M v =303.14), the molar ratio of PEO to metal salt is 20:1, 15.0% PrOx-V0 of the total mass of polymer matrix and metal salt is added, and stirred at room temperature for 24 hours; then poured into a polytetrafluoroethylene mold, allowed to stand at room temperature for 24 hours to evaporate a large amount of solvent; then vacuum dried at 60°C for 24 hours to obtain a composite solid electrolyte containing 15.0% PrOx-V0.
[0078] 2. The preparation method of the positive electrode sheet is the same as that of Example 1.
[0079] 3. Assemble the positive electrode sheet, the sodium metal sheet and the above-mentioned composite solid electrolyte into an all-solid-state sodium metal battery in a glove box filled with argon (O2, H2O content are both <0.1ppm).
[0080] Comparative Example 1
[0081] 1. Referring to Examples 1-4, a PEO solid electrolyte prepared without adding a PrOx-V0 additive, that is, a PEO solid electrolyte containing PEO and a sodium salt is used as Comparative Example 1. The specific operation is as follows: in a glove box filled with argon, acetonitrile is used as a solvent, 0.3445 g of sodium bistrifluoromethanesulfonimide (NaTFSI) and 1.0 g of polyethylene oxide (PEO) in a molar ratio of 1:20 are dissolved in 15 mL of acetonitrile solvent, the solvent is naturally evaporated after standing for 24 hours, and vacuum dried at 60° C. for 24 hours to obtain a PEO-based solid electrolyte containing no PrOx-V0 additive but containing a sodium salt.
[0082] 2. The preparation method of the positive electrode sheet is the same as that of Example 1.
[0083] 3. Assemble the positive electrode sheet, the sodium metal sheet and the above-mentioned composite solid electrolyte into an all-solid-state sodium metal battery in a glove box filled with argon (O2, H2O content are both <0.1ppm).
[0084] The batteries prepared in Examples 1-4 and Comparative Example 1 were placed in a constant temperature and humidity chamber at 60°C for 12 hours, and then subjected to a charge and discharge cycle test on a Blue Electric Test Charge and Discharge Tester. The test conditions were: within a voltage range of 2.0-4.0V, a rate of 0.05-1C, a charge and discharge rate test at 25°C, and a cycle test at 0.2C (0.1C = 129 mAh g-1 ) Charge and discharge for 200 cycles. The results are shown in Table 1-2.
[0085] Table 1 Cycling performance of sodium iron pyrophosphate solid-state battery assembled with electrolyte membrane of Examples 1-4 and Comparative Example 1
[0086]
[0087] Table 2 Rate cycling performance of sodium iron pyrophosphate solid-state battery assembled with electrolyte membranes of Examples 1-4 and Comparative Example 1
[0088]
[0089] Table 3 Ionic conductivity of electrolytes of Example 2 and Comparative Example 1 at different temperatures
[0090] Example 2 Comparative Example 1 30℃ <![CDATA[3.24×10 -5 Scm -1 ]]> <![CDATA[8.46×10 -6 Scm -1 ]]> 40℃ <![CDATA[6.89×10 -4 Scm -1 ]]> <![CDATA[2.16×10 -5 Scm -1 <!-- 6 -->]]> 50℃ <![CDATA[1.37×10 -4 Scm -1 ]]> <![CDATA[6.44×10 -5 Scm -1 ]]> 60℃ <![CDATA[4.99×10 -4 Scm -1 ]]> <![CDATA[2.27×10 -5 Scm -1 ]]>
[0091] Comparative Analysis
[0092] As can be seen from Table 1, the cycle performance of the sodium iron pyrophosphate solid-state battery assembled using the solid electrolyte containing the PrOx-V0 additive prepared in Examples 1-4 of the present invention is significantly improved (compared with Comparative Example 1), and the discharge specific capacity of the battery is significantly improved with the increase of the PrOx-V0 additive in the composite solid electrolyte. When the content of the additive PrOx-V0 is 5.0%, the battery exhibits the best discharge specific capacity and cycle stability, which is mainly attributed to the strong affinity of oxygen vacancies with salt anions, which promotes the dissociation of sodium salts, and the rapid migration of sodium ions improves the ionic conductivity of the electrolyte, making the battery capacity performance excellent.
[0093] It can be seen from Table 2 that the sodium iron pyrophosphate solid-state battery assembled with a composite solid electrolyte containing 5.0% PrOx-V0 additive has a higher discharge specific capacity than Comparative Example 1 and Example 1 at multiple rates of 0.05C, 0.1C, 0.2C, 0.5C and 1C. Figure 1-4 and Figure 5 Table 3 is a multi-rate charge and discharge curve diagram of the batteries of Examples 1-4 of the present invention and Comparative Example 1. It shows that the 5.0% PrOx-V0 additive can improve the ionic conductivity of sodium ions, thereby reducing the polarization inside the battery and improving the rate performance of the battery.
[0094] The PrOx-V0 material used in this embodiment is used as an additive for the polymer solid electrolyte. There is a strong interaction between its surface oxygen vacancies and sodium salt anions, which changes the environment of local sodium ions and promotes the dissociation of sodium salts and the migration of sodium ions. At the same time, the introduction of PrOx-V0 catalyst in the polymer can increase the concentration of sodium ion conductive amorphous in the polymer phase and accelerate the migration of sodium ions on the polymer chain segments. In addition, PrOx-V0 can also optimize the interface stability, promote the dissociation of sodium salts, and make the salt anions form a NaF-rich protective layer on the surface of the metal sodium electrode, so as to achieve a more uniform sodium deposition at the interface. At the same time, PrOx-V0 is evenly dispersed in PEO, so that the composite electrolyte membrane has good mechanical strength, can significantly inhibit the growth of sodium surface dendrites, enhance the interface compatibility between the electrode and the electrolyte, and obtain an all-solid-state metal sodium battery with better cycle performance.
[0095] The above content is a specific description of the content of the present invention in combination with a preferred embodiment, but it cannot be determined that the specific implementation of the present invention is limited to the embodiment. For those skilled in the art who understand the field to which the present invention belongs, several evolutions and substitutions can be made without departing from the research ideas of the present invention, and these deductions and substitutions are all included in the scope defined by the claims of the present invention.
Claims
1. A composite solid electrolyte containing an oxygen vacancy catalyst, characterized in that: The composite solid electrolyte comprises a polymer, a metal sodium salt, and an inorganic additive, wherein the inorganic additive is an oxygen-containing vacancy catalyst PrOx-V0, and the ratio of the mass of the inorganic additive to the total mass of the polymer and the metal sodium salt is 1-15:
100.
2. A composite solid electrolyte containing an oxygen vacancy catalyst according to claim 1, characterized in that: The polymer is one or more of polyethylene oxide, poly(vinylidene fluoride-co-hexafluoropropylene), polymethyl methacrylate, and polyacrylonitrile, and the metal sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bis(trifluoromethanesulfonyl imide), and sodium bis(difluorosulfonyl imide).
3. A composite solid electrolyte containing an oxygen vacancy catalyst as claimed in claim 1 or 2, characterized in that: The composite solid electrolyte consists of polyethylene oxide, sodium bis(trifluoromethanesulfonyl)imide and PrOx-V0.
4. The composite solid electrolyte containing oxygen vacancy catalyst according to claim 1, characterized in that: The ratio of the mass of the inorganic additive to the total mass of the polymer and the metal sodium salt is 5:
100.
5. A method for preparing a composite solid electrolyte containing an oxygen vacancy catalyst according to any one of claims 1 to 4, characterized in that: The method is: Step 1: Preparation of oxygen vacancy catalyst PrOx-V0: (1) preparing a solution of a metal salt containing Pr with a concentration of 0.02-0.05M, using a mixed solvent of water and ethanol in a volume ratio of 1:1-4 as a solvent, placing the solution in a hydrothermal kettle, adding urea, stirring and mixing at room temperature to obtain a light green mixture; the mass ratio of the metal salt containing Pr to urea is 1:1-4; (2) Slowly add NaOH solution to the above solution to adjust the pH value to between 8.5 and 9.5, and then continue stirring for 1 hour; (3) closing the hydrothermal reactor, placing it in an oven at 120-160° C., heating it for 1-4 h, cooling it naturally, collecting the precipitate by centrifugation, and drying it in an oven at 60° C. overnight to obtain a precursor; (4) placing the precursor in a tube furnace, heating it to 450-650° C. in an inert atmosphere, calcining it for 2-6 hours, and grinding it after natural cooling to obtain an oxygen vacancy catalyst PrOx-V0; Step 2: Preparation of composite solid electrolyte: First, completely dissolve the polymer, metal sodium salt and oxygen vacancy catalyst in a volatile solvent, stir and mix them thoroughly at room temperature, pour the resulting mixed solution into a mold, let it stand at room temperature to allow the solvent to evaporate naturally, and finally transfer it to a vacuum drying oven, heat it to 60-80°C and dry it for 10-12 hours. After cutting, a composite solid electrolyte containing oxygen vacancy catalyst is obtained.
6. The method for preparing a composite solid electrolyte containing an oxygen vacancy catalyst according to claim 5, characterized in that: In step 1 (1), the metal salt containing Pr is one or more of praseodymium nitrate hexahydrate, praseodymium oxalate decahydrate, praseodymium phosphate, and praseodymium sulfate octahydrate.
7. The method for preparing a composite solid electrolyte containing an oxygen vacancy catalyst according to claim 5, characterized in that: In step 2, the volatile solvent is acetonitrile, dimethylformamide, anisole, dichloroethane, etc.
8. Use of a composite solid electrolyte containing oxygen vacancy catalyst according to any one of claims 1 to 4, characterized in that: The composite solid electrolyte is used in the preparation of an all-solid-state metal sodium battery, which comprises a composite solid electrolyte, a metal sodium negative electrode and a positive electrode.
9. The use of a composite solid electrolyte containing an oxygen vacancy catalyst as claimed in claim 8, characterized in that: The metallic sodium negative electrode is one of metallic sodium foil, sodium sheet, sodium alloy, hard carbon or titanium-based negative electrode; the positive electrode is a composite of positive electrode active material, binder and conductive agent coated on a current collector.
10. The use of a composite solid electrolyte containing an oxygen vacancy catalyst as claimed in claim 8, characterized in that: The current collector is aluminum foil, carbon-coated aluminum foil or stainless steel foil; the positive electrode active material is at least one of sodium iron phosphate, sodium vanadium phosphate, sodium titanium phosphate, sodium iron sulfate, sodium iron pyrophosphate, sodium ion fluorophosphate, sodium manganese oxide, and sodium vanadium fluorophosphate; the binder is at least one of polyvinylidene fluoride, polyamide, polyvinyl alcohol, and carboxymethyl cellulose; the conductive agent is at least one of carbon black, Ketjen black, and super P.
